Mutual Recognition Procedure for the Registration of Medicines: New Challenges or Opportunities - A. V. Foteeva; O. S. Barshadskaya; N. B. Rostova (Разработка и регистрация лекарственных средств, 2022)
Introduction. An important task for pharmaceutical manufacturers is to bring high quality, effective and safe medicines to the market. In the event that the country's resources are not enough, drugs that have been successfully registered in other countries come to the rescue.Aim. To study the possibilities and advantages of the procedure of mutual recognition of registration medicinal products as a potential for the development of domestic producers.Materials and methods. The materials of the study were available publications in peer-reviewed journals on thematic queries based on keywords of the selected topic, official websites, regulatory legal acts, regulating the procedure for registering medicinal products in the EU and the Russian Federation.Results and discussion. New approaches to registration within the framework of the Eurasian Economic Union (using the example of the mutual recognition procedure) are considered from the perspective of new opportunities and emerging problems for domestic manufacturers of generic drugs. A comparative analysis of the mutual recognition procedure and the national procedure for registration of medicinal products revealed a number of advantages for domestic manufacturers, favoring the introduction of medicinal products into circulation on the territory of the EAEU.Conclusion. The review of the process of harmonization of the registration practice of medicinal products in the EAEU speaks of the prospects of using the mutual recognition procedure for developing the potential of domestic manufacturers and facilitating access to effective and safe drugs.